ASSESSMENT COMPLIANCE WITH ISO37001:2019 ANTI-BRIBERY MANAGEMENT SYSTEM REQUIREMENTS-A CASE STUDY IN THE IRAQI INTEGRITY COMMISSION - Hayder jabber jasim; Raoudha Kammoun (American Journals, 2024)
The research aims to identify the extent to which the requirements of the anti-bribery management system are available in accordance with the standard (ISO 37001:2019) in the Integrity Commission, by evaluating the Commission’s actual compliance with the requirements of the standard. In order to achieve this goal, the case study approach was adopted and the checklist was adopted for the purpose of measuring the gap The results of the research showed that the reality of applying the anti-bribery system in the authority compared to the requirements of the standard has reached 45%, which is close to being partially applied and undocumented, and this indicates that there is a gap of 55%, which can be addressed through continuous improvements and management review of the system and solving documentation and application problems For some requirements, especially since the Central Bank is in its infancy to implement the system.
Keywords: Anti-bribery system 37001-2019, ISO